Applications of airborne ultrasonic technology in the food industry. (September 2017) - Charoux, Clémentine M.G.; Ojha, Kumari Shikha; O'Donnell, Colm P.; Cardoni, Andrea; Tiwari, Brijesh K.
Abstract: Ultrasound has been widely investigated for food processing applications. To date studies have been mainly carried out using contact-type ultrasound systems. Recently it has been demonstrated that ultrasonic waves propagated via gases including air using non-contact ultrasound devices may also be employed to enhance various food processes with minimal impact on food quality. Airborne acoustic ultrasound has been shown to be suitable for various food and non-food applications including drying, defoaming and decontamination. This novel technology is currently being actively investigated to increase the limited knowledge on the specific mechanisms involved in airborne ultrasound assisted operations. Some of the main challenges that have hampered efficient energy transmission through air have been addressed by the development of new types of transducers. The objective of this review is to outline various potential applications of airborne ultrasound including drying, defoaming and inactivation of microorganisms. Equipment types, mechanisms and challenges encountered are also discussed. Highlights: Airborne acoustic ultrasound as an emerging food processing technology. Equipment and systems of non-contact transducers. Applications in the food industry: drying, defoaming and inactivation of microorganisms – review and mechanisms. Processing and application challenges.